Water-resistant aluminum alloy core photovoltaic cable and preparation process thereof
By using modified epoxy resins and copolymers in cable sheath fillers, combining perfluorooctanesulfonic acid surface-modified silica and copolymers of neopentyl glycol monoester with butyl glycidyl ether, the problem of water absorption and swelling of the cable in a wet environment is solved, achieving higher water resistance and mechanical strength.
Patent Information
- Application Number
- CN202510286380.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-12
AI Technical Summary
When existing cables are used in a coastal humid environment, the water barrier layer material is prone to absorb water and swell, resulting in gaps between the cable core layer and the sheath, reducing conductivity, and ordinary cable fillers cannot take into account both flexibility and water resistance.
Modified epoxy resin and copolymer are used as cable sheath fillers, and the silica surface is modified by perfluorooctane sulfonic acid to increase hydrophobicity, and neopentyl glycol monoester and butyl glycidyl ether are added to the filler to form a copolymer with excellent anti-hydrolysis and anti-oxidation properties.
It significantly improves the water resistance and mechanical strength of the cable, extends the service life of the cable, and maintains good insulation performance in high humidity environments.
Smart Images

Figure CN119811804A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cable preparation, and in particular to a water-resistant aluminum alloy core photovoltaic cable and a preparation process thereof. Background Art
[0002] The structure of a cable usually consists of multiple parts, including cable core, insulation layer, filler and outer sheath. Among them, the cable core material includes copper wire core and aluminum alloy wire core. Copper wire core is the most common cable core material, with excellent conductivity and good mechanical properties, but it is heavy. Aluminum alloy wire core is made of aluminum and other metals alloyed, with good conductivity and mechanical strength, lighter than copper wire core, and strong corrosion resistance, suitable for use in harsh environments.
[0003] Therefore, aluminum alloy cables need to have better environmental resistance, such as heat resistance, cold resistance or water resistance. Among them, water-resistant cables have certain hydrophobicity because the cable sheath itself is made of materials such as polyvinyl chloride. Therefore, functional materials that improve water resistance are often not added to the cable sheath and filler. However, in underwater operations, coastal areas and submarine cable laying scenarios, cables need to be used in humid environments for a long time. In underwater environments and submarine cable laying, moisture can be directly blocked by adding a waterproof shell. However, in coastal areas, the cost of directly installing a waterproof shell is relatively high. Long-term exposure to high air humidity can easily lead to a decrease in cable insulation. At this time, a water-blocking layer will be set inside the cable to prevent moisture penetration. However, the water-blocking layer material usually has a strong Moisture absorption capacity. Once used in a humid environment for a long time, water absorption, swelling and aging will occur, resulting in gaps between the cable core layer and the sheath. These gaps are prone to produce local high electric field strength, resulting in air gap breakdown and local discharge, thereby greatly reducing the conductivity of the cable. Although ordinary cable fillers have good filling capacity and will not expand after long-term use, they cannot take into account both flexibility and water resistance. Therefore, a cable filler with better water-proof ability is needed to ensure that the cable can be used for a long time in a humid coastal environment, and to overcome the problem of gaps in the water-blocking layer due to long-term use, so as to extend the service life as much as possible. Therefore, the present invention provides a water-resistant aluminum alloy core photovoltaic cable and a preparation process thereof to solve the above problems. Summary of the invention
[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a water-resistant aluminum alloy core photovoltaic cable and a preparation process thereof.
[0005] A preparation process of a water-resistant aluminum alloy core photovoltaic cable comprises the following steps: S1: Preparation of modified epoxy resin Adding silica and perfluorooctane sulfonic acid together into deionized water, and then adding silane coupling agent KH570, after the reaction is completed, obtaining silica surface modified with perfluorooctane sulfonic acid, weighing epoxy resin, silica surface modified with perfluorooctane sulfonic acid and silane coupling agent KH550, adding them into anhydrous ethanol for reaction, and then removing the solvent to obtain modified epoxy resin; S2: Preparation of copolymers from hydroxypivalic acid neopentyl glycol monoester and butyl glycidyl ether Weigh hydroxypivalic acid neopentyl glycol monoester into a reaction bottle, add anhydrous methanol to dissolve, evacuate and pass nitrogen, add potassium methoxide and anhydrous methanol into the reaction bottle, heat up, add glycerol and butyl glycidyl ether into the reaction bottle together, stir, add anhydrous methanol to the product for dialysis, and dry to obtain a copolymer; S3: Preparation of cable sheath filler Weigh magnesium hydroxide, deionized water and sodium oleate, pour them into a three-necked flask in sequence, and after the reaction is complete, obtain modified magnesium hydroxide, weigh modified epoxy resin, add it into a reactor, then heat the reactor, stir it magnetically, then add modified magnesium hydroxide, palygorskite powder, cotton fiber, hollow glass microbeads and silane coupling agent KH550 in sequence, disperse them by ultrasonic, then add Tween 80, 593 curing agent and copolymer, stir evenly, pour into a mold and solidify, and obtain a sheath filler; S4: Preparation of water-resistant aluminum alloy core photovoltaic cables Aluminum alloy is used as the cable core material, the outer layer of the cable core material is wrapped with an insulating layer, the outer layer is filled with the sheath filler prepared in step S3, and the outermost layer is wrapped with a cable sheath to obtain a water-resistant aluminum alloy core photovoltaic cable.
[0006] Furthermore, step S1 of preparing the modified epoxy resin comprises the following steps: S1.1: Add 10-15 parts by mass of silica and 20-25 parts by mass of perfluorooctane sulfonic acid to 75-85 parts by mass of deionized water, perform ultrasonic treatment for 20-25 minutes, then add 2-5 parts by mass of silane coupling agent KH570, and react for 3-4 hours in a water bath at 40-50°C. After the reaction is completed, pour out the liquid in the flask, filter it, wash it, dry it, and grind it to obtain perfluorooctane sulfonic acid surface-modified silica, which is stored for later use; S1.2: Weigh 50-60 parts by mass of epoxy resin, 2-5 parts by mass of perfluorooctane sulfonic acid surface-modified silica and 15-20 parts by mass of silane coupling agent KH550, add them to 75-90 parts by mass of anhydrous ethanol, heat to 50-60°C in a water bath, maintain stirring at a speed of 50-60r / min, react for 4-5h, then remove the solvent anhydrous ethanol, wash and dry to obtain the modified epoxy resin.
[0007] Further, step S2, preparing a copolymer from hydroxypivalic acid neopentyl glycol monoester and butyl glycidyl ether comprises the following steps: S2.1: Weigh 2-3 parts by weight of neopentyl glycol monohydroxypivalate into a reaction bottle, add 8-10 parts by weight of anhydrous methanol, dissolve, and evacuate and pass nitrogen; S2.2: Mix potassium methoxide and anhydrous methanol at a solid-liquid ratio of (0.5-1) g:2 mL and add them to the reaction bottle, then stir for 2-2.5 h, and then remove the solvent methanol; S2.3: Heat the reaction bottle to 90-95°C, mix 0.5-1 parts by mass of glycerol and 1-2 parts by mass of butyl glycidyl ether, add them into the reaction bottle, and stir mechanically at a speed of 100-120 r / min for 12-13 hours; S2.4: Then terminate the reaction, add 10-15 parts by mass of anhydrous methanol to the product and mix well, then dialyze using a dialysis bag with a molecular weight cutoff of 1200 g / mol, use methanol for 48-50 hours, then use a rotary evaporator to spin dry the methanol, and put it into a vacuum drying oven at 40-45°C to obtain a copolymer.
[0008] Furthermore, step S3 of preparing a cable sheath filler comprises the following steps: S3.1: Weigh 7-8 parts by mass of magnesium hydroxide, 90-95 parts by mass of deionized water and 4-5 parts by mass of sodium oleate, pour them into a three-necked flask in sequence, react in a water bath at 40-45°C for 2-3 hours, and after the reaction is complete, pour out the liquid in the flask, filter it, wash, dry it, and grind it to obtain modified magnesium hydroxide for standby use; S3.2: Weigh 10-15 parts by mass of modified epoxy resin, add it into the reactor, then heat the reactor to 40-45°C, stir it magnetically for 15-20 minutes, then add 0.5-1.5 parts by mass of modified magnesium hydroxide, 0.5-1 parts by mass of palygorskite powder, 0.2-0.6 parts by mass of cotton fiber, 1-3 parts by mass of hollow glass microspheres and 1-3 parts by mass of silane coupling agent KH550 in sequence, continue stirring at 40-50°C for 2-3 hours, and then ultrasonically disperse for 30-35 minutes; S3.3: After uniform dispersion, add 0.1-0.3 parts by mass of Tween 80, 2.5-3 parts by mass of 593 curing agent and 6-10 parts by mass of copolymer, stir evenly and pour into a mold to solidify to obtain a sheath filler.
[0009] Furthermore, the silane coupling agent KH550 is specifically a functional material modifier with γ-aminopropyltriethoxysilane as a main component.
[0010] Furthermore, Tween 80 is specifically a polyoxyethylene sorbitan monooleate nonionic surfactant.
[0011] Furthermore, the 593 curing agent is specifically a modified amine curing agent synthesized by reacting diethylenetriamine and butyl glycidyl ether.
[0012] Furthermore, the insulating layer is made of one of polyethylene, cross-linked polyethylene and polypropylene.
[0013] Furthermore, the cable sheath is made of one of thermoplastic polyurethane elastomer rubber, silicone rubber, chlorinated polyethylene and polyvinyl chloride materials.
[0014] A water-resistant aluminum alloy core photovoltaic cable is prepared by the above-mentioned preparation process of the water-resistant aluminum alloy core photovoltaic cable.
[0015] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention prepares a copolymer by using hydroxypivalic acid neopentyl glycol monoester and butyl glycidyl ether. The hydroxypivalic acid neopentyl glycol monoester contains a hydroxyl bond and an ester bond, wherein the hydroxyl bond can undergo a ring-opening reaction with the epoxy group of butyl glycidyl ether to form a new ether bond. In addition, the hydroxypivalic acid neopentyl glycol monoester also contains a quaternary carbon atom. This structure makes the ester group very stable. The presence of the quaternary carbon atom increases the steric hindrance effect of the ester group, thereby inhibiting the occurrence of the hydrolysis reaction, so that the copolymer has excellent anti-hydrolysis and anti-oxidation properties. At the same time, the molecular skeleton of the hydroxypivalic acid neopentyl glycol monoester has It has good flexibility and can form an active diluent through chemical bonding with butyl glycidyl ether. It is used in epoxy resin to reduce the viscosity of epoxy resin and improve its fluidity. The combination of the two participates in the curing reaction, which not only improves the flexibility of epoxy resin, but also significantly improves its impact strength and heat resistance. The high-flexibility filler fills the gaps inside the cable, reduces the air gap, and prevents the overall insulation performance of the cable. The good heat resistance of the filler enables it to maintain good mechanical properties in the high temperature environment caused by long-term use of the cable, thereby extending the service life of the cable.
[0016] 2. The present invention utilizes perfluorooctane sulfonic acid to modify the surface of silica, and uses the obtained perfluorooctane sulfonic acid surface-modified silica to modify epoxy resin. The surface of silica is first treated with KH-570, and then perfluorooctane sulfonic acid is introduced to react with the hydroxyl groups on the surface of silica by chemical bonding to form a stable silicon-oxygen bond, thereby fixing the perfluorooctane sulfonic acid group on the surface of silica. The free energy of the surface of silica modified by perfluorooctane sulfonic acid is reduced, and the dispersion performance is better, and it can be evenly dispersed in the epoxy resin. In addition, the perfluorooctane sulfonic acid group has excellent hydrophobicity, which can reduce the absorption of external moisture by the epoxy resin, prevent moisture from further invading the interior of the cable, ensure the dryness of the metal material of the cable core, and thus ensure that the cable has good water resistance.
[0017] 3. In the preparation of the cable filler between the cable sheath and the insulating layer, the present invention also adds palygorskite powder and cotton fiber. After being added to the modified resin through the action of the curing agent and the surfactant, the modified resin can be used as an adhesive to tightly combine the palygorskite and the cotton fiber. Both the palygorskite and the cotton fiber have good mechanical strength and fibrous structure. The two can show better mechanical strength and tensile capacity in the longitudinal direction through the bonding of the modified resin, so that the cable filler has excellent flexibility and tensile capacity, thereby extending the service life of the cable. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0019] Figure 1 The present invention is a flow chart of a process for preparing a water-resistant aluminum alloy core photovoltaic cable used in an embodiment of the present invention. DETAILED DESCRIPTION
[0020] The following is a detailed description of a water-resistant aluminum alloy core photovoltaic cable and its preparation process provided by the present invention in combination with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0021] Embodiment 1:
[0022] A preparation process of a water-resistant aluminum alloy core photovoltaic cable, such as Figure 1 As shown, the following steps are included: S1: Preparation of modified epoxy resin S1.1: 10 parts by mass of silica and 20 parts by mass of perfluorooctane sulfonic acid were added to 75 parts by mass of deionized water, and ultrasonicated for 20 minutes. Then, 2 parts by mass of silane coupling agent KH570 were added, and the reaction was carried out in a water bath at 40°C for 3 hours. After the reaction was completed, the liquid in the flask was poured out, filtered, washed, dried, and then ground to obtain perfluorooctane sulfonic acid surface-modified silica, which was stored for later use; S1.2: Weigh 50 parts by mass of epoxy resin, 2 parts by mass of perfluorooctane sulfonic acid surface-modified silica and 15 parts by mass of silane coupling agent KH550, add them to 75 parts by mass of anhydrous ethanol, heat to 50°C in a water bath, maintain stirring at a speed of 50 r / min, react for 4 hours, then remove the solvent anhydrous ethanol, wash and dry to obtain the modified epoxy resin.
[0023] S2: Preparation of copolymer from hydroxypivalic acid neopentyl glycol monoester and butyl glycidyl ether S2.1: Weigh 2 parts by mass of neopentyl glycol monohydroxypivalate into a reaction bottle, add 8 parts by mass of anhydrous methanol, dissolve, and evacuate and pass nitrogen; S2.2: Mix potassium methoxide and anhydrous methanol at a solid-liquid ratio of 0.5 g:2 mL, add them into the reaction bottle, stir for 2 h, and then remove the solvent methanol; S2.3: Heat the reaction bottle to 90°C, mix 0.5 parts by mass of glycerol and 1 part by mass of butyl glycidyl ether, add them into the reaction bottle, and stir mechanically at a speed of 100 r / min for 12 hours; S2.4: Then, the reaction was terminated, and 10 parts by mass of anhydrous methanol was added to the product and mixed evenly. The product was dialyzed using a dialysis bag with a molecular weight cutoff of 1200 g / mol. The methanol was dialyzed for 48 hours. The methanol was then dried using a rotary evaporator and dried in a vacuum drying oven at 40°C to obtain a copolymer.
[0024] S3: Preparation of cable sheath filler S3.1: Weigh 7 parts by mass of magnesium hydroxide, 90 parts by mass of deionized water and 4 parts by mass of sodium oleate, pour them into a three-necked flask in sequence, and react in a water bath at 40°C for 2 hours. After the reaction is complete, pour out the liquid in the flask, filter it, wash it, dry it, and grind it to obtain modified magnesium hydroxide for standby use; S3.2: Weigh 10 parts by mass of modified epoxy resin and add it into the reactor, then heat the reactor to 40°C, stir it magnetically for 15 minutes, then add 0.5 parts by mass of modified magnesium hydroxide, 0.5 parts by mass of palygorskite powder, 0.2 parts by mass of cotton fiber, 1 part by mass of hollow glass microspheres and 1 part by mass of silane coupling agent KH550 in sequence, continue stirring at 40°C for 2 hours, and then ultrasonically disperse for 30 minutes; S3.3: After uniform dispersion, add 0.1 parts by mass of Tween 80, 2.5 parts by mass of 593 curing agent and 6 parts by mass of copolymer, stir evenly and pour into a mold to solidify to obtain a sheath filler.
[0025] S4: Preparation of water-resistant aluminum alloy core photovoltaic cables Aluminum alloy is used as the cable core material, the outer layer of the cable core material is wrapped with an insulating layer, the insulating layer is a polyethylene material, the outer layer is filled with the sheath filler prepared in step S3, and the outermost layer is wrapped with a cable sheath, the cable sheath is a thermoplastic polyurethane elastomer rubber material, to obtain a water-resistant aluminum alloy core photovoltaic cable.
[0026] Example 2
[0027] A preparation process of a water-resistant aluminum alloy core photovoltaic cable, such as Figure 1 As shown, the following steps are included: S1: Preparation of modified epoxy resin S1.1: 15 parts by mass of silica and 25 parts by mass of perfluorooctane sulfonic acid were added to 85 parts by mass of deionized water, and ultrasonicated for 20 minutes. Then, 5 parts by mass of silane coupling agent KH570 were added, and the reaction was carried out in a water bath at 40°C for 3 hours. After the reaction was completed, the liquid in the flask was poured out, filtered, washed, dried, and then ground to obtain perfluorooctane sulfonic acid surface-modified silica, which was stored for later use; S1.2: Weigh 60 parts by mass of epoxy resin, 5 parts by mass of perfluorooctane sulfonic acid surface-modified silica and 20 parts by mass of silane coupling agent KH550, add them to 90 parts by mass of anhydrous ethanol, heat to 50°C in a water bath, maintain stirring at a speed of 50 r / min, react for 4 hours, then remove the solvent anhydrous ethanol, wash and dry to obtain the modified epoxy resin.
[0028] S2: Preparation of copolymers from hydroxypivalic acid neopentyl glycol monoester and butyl glycidyl ether S2.1: Weigh 3 parts by mass of neopentyl glycol monohydroxypivalate into a reaction bottle, add 10 parts by mass of anhydrous methanol, dissolve, and evacuate and pass nitrogen; S2.2: Mix potassium methoxide and anhydrous methanol at a solid-liquid ratio of 0.5 g:2 mL, add them into the reaction bottle, stir for 2 h, and then remove the solvent methanol; S2.3: Heat the reaction bottle to 90°C, mix 1 part by mass of glycerol and 2 parts by mass of butyl glycidyl ether, add them into the reaction bottle, and stir mechanically at a speed of 100 r / min for 12 h; S2.4: Then, the reaction was terminated, and 15 parts by mass of anhydrous methanol was added to the product and mixed evenly. The product was dialyzed using a dialysis bag with a molecular weight cutoff of 1200 g / mol. The methanol was dialyzed for 48 hours. The methanol was then dried using a rotary evaporator and dried in a vacuum drying oven at 40°C to obtain a copolymer.
[0029] S3: Preparation of cable sheath filler S3.1: Weigh 8 parts by mass of magnesium hydroxide, 95 parts by mass of deionized water and 5 parts by mass of sodium oleate, pour them into a three-necked flask in sequence, and react in a water bath at 40°C for 2 hours. After the reaction is complete, pour out the liquid in the flask, filter it, wash it, dry it, and grind it to obtain modified magnesium hydroxide for standby use; S3.2: Weigh 15 parts by mass of modified epoxy resin and add it to the reactor, then heat the reactor to 40°C and stir it magnetically for 15 minutes, then add 0.5 parts by mass of modified magnesium hydroxide, 1 part by mass of palygorskite powder, 0.6 parts by mass of cotton fiber, 3 parts by mass of hollow glass microspheres and 3 parts by mass of silane coupling agent KH550 in sequence, continue stirring at 40°C for 2 hours, and then ultrasonically disperse for 30 minutes; S3.3: After uniform dispersion, add 0.3 parts by mass of Tween 80, 3 parts by mass of 593 curing agent and 10 parts by mass of copolymer, stir evenly and pour into a mold to solidify to obtain a sheath filler.
[0030] S4: Preparation of water-resistant aluminum alloy core photovoltaic cables Aluminum alloy is used as the cable core material, the outer layer of the cable core material is wrapped with an insulating layer, the insulating layer is a polyethylene material, the outer layer is filled with the sheath filler prepared in step S3, and the outermost layer is wrapped with a cable sheath, the cable sheath is a thermoplastic polyurethane elastomer rubber material, to obtain a water-resistant aluminum alloy core photovoltaic cable.
[0031] Example 3
[0032] A preparation process of a water-resistant aluminum alloy core photovoltaic cable, such as Figure 1 As shown, the following steps are included: S1: Preparation of modified epoxy resin S1.1: 10 parts by mass of silica and 20 parts by mass of perfluorooctane sulfonic acid were added to 75 parts by mass of deionized water, and ultrasonicated for 25 minutes. Then, 2 parts by mass of silane coupling agent KH570 were added, and the reaction was carried out in a water bath at 50°C for 4 hours. After the reaction was completed, the liquid in the flask was poured out, filtered, washed, dried, and then ground to obtain perfluorooctane sulfonic acid surface-modified silica, which was stored for later use; S1.2: Weigh 50 parts by mass of epoxy resin, 2 parts by mass of perfluorooctane sulfonic acid surface-modified silica and 15 parts by mass of silane coupling agent KH550, add them to 75 parts by mass of anhydrous ethanol, heat to 60°C in a water bath, maintain stirring at a speed of 60 r / min, react for 5 hours, then remove the solvent anhydrous ethanol, wash and dry to obtain the modified epoxy resin.
[0033] S2: Preparation of copolymers from hydroxypivalic acid neopentyl glycol monoester and butyl glycidyl ether S2.1: Weigh 2 parts by mass of neopentyl glycol monohydroxypivalate into a reaction bottle, add 8 parts by mass of anhydrous methanol, dissolve, and evacuate and pass nitrogen; S2.2: Mix potassium methoxide and anhydrous methanol at a solid-liquid ratio of 0.5 g:2 mL, add them to the reaction bottle, stir for 2.5 h, and then remove the solvent methanol; S2.3: Heat the reaction bottle to 95°C, mix 0.5 parts by mass of glycerol and 1 part by mass of butyl glycidyl ether, add them into the reaction bottle, and stir mechanically at a speed of 120 r / min for 13 h; S2.4: Then, the reaction was terminated, and 10 parts by mass of anhydrous methanol was added to the product and mixed evenly. The product was dialyzed using a dialysis bag with a molecular weight cutoff of 1200 g / mol. The methanol was dialyzed for 50 hours. The methanol was then dried using a rotary evaporator and dried in a vacuum drying oven at 45°C to obtain a copolymer.
[0034] S3: Preparation of cable sheath filler S3.1: Weigh 7 parts by mass of magnesium hydroxide, 90 parts by mass of deionized water and 4 parts by mass of sodium oleate, pour them into a three-necked flask in sequence, and react in a water bath at 50°C for 3 hours. After the reaction is complete, pour out the liquid in the flask, filter it, wash it, dry it, and grind it to obtain modified magnesium hydroxide for standby use; S3.2: Weigh 10 parts by mass of modified epoxy resin and add it into the reactor, then heat the reactor to 45°C and stir it magnetically for 20 minutes, then add 0.5 parts by mass of modified magnesium hydroxide, 0.5 parts by mass of palygorskite powder, 0.2 parts by mass of cotton fiber, 1 part by mass of hollow glass microspheres and 1 part by mass of silane coupling agent KH550 in sequence, continue stirring at 50°C for 3 hours, and then ultrasonically disperse for 35 minutes; S3.3: After uniform dispersion, add 0.1 parts by mass of Tween 80, 2.5 parts by mass of 593 curing agent and 6 parts by mass of copolymer, stir evenly and pour into a mold to solidify to obtain a sheath filler.
[0035] S4: Preparation of water-resistant aluminum alloy core photovoltaic cables Aluminum alloy is used as the cable core material, the outer layer of the cable core material is wrapped with an insulating layer, the insulating layer is a polyethylene material, the outer layer is filled with the sheath filler prepared in step S3, and the outermost layer is wrapped with a cable sheath, the cable sheath is a thermoplastic polyurethane elastomer rubber material, to obtain a water-resistant aluminum alloy core photovoltaic cable.
[0036] Comparative Example 1: Compared with Example 1, the difference of Comparative Example 1 is that step S1.1 is not performed, and silica is used instead of perfluorooctane sulfonic acid surface-modified silica in step S1.2, specifically "S1.2: weigh 50 parts by mass of epoxy resin, 2 parts by mass of silica and 15 parts by mass of silane coupling agent KH550, add them to 75 parts by mass of anhydrous ethanol, heat to 50°C in a water bath, maintain stirring at a speed of 50 r / min, react for 4 hours, then remove the solvent anhydrous ethanol, wash and dry to obtain modified epoxy resin", and the other steps remain unchanged, and the prepared water-resistant aluminum alloy core photovoltaic cable is recorded as Comparative Example 1.
[0037] Comparative Example 2: Compared with Example 1, the difference of Comparative Example 2 is that perfluorooctane sulfonic acid is not added in step S1.1, but perfluorooctanoic acid is used instead of perfluorooctane sulfonic acid, specifically "S1.1: add 10 parts by mass of silica and 20 parts by mass of perfluorooctanoic acid together into 75 parts by mass of deionized water, ultrasonicate for 20 minutes, then add 2 parts by mass of silane coupling agent KH570, and react for 3 hours in a water bath at 40°C. After the reaction is completed, pour out the liquid in the flask, filter, wash, dry and grind to obtain perfluorooctane sulfonic acid surface modified silica, and store it for later use", and the other steps remain unchanged, and the prepared water-resistant aluminum alloy core photovoltaic cable is recorded as 2.
[0038] Comparative Example 3: Compared with Example 1, the difference of Comparative Example 3 is that step S2 is not performed, and butyl glycidyl ether is used instead of the copolymer in step S3, specifically "S3.3: after uniform dispersion, add 0.1 mass parts of Tween 80, 2.5 mass parts of 593 curing agent and 6 mass parts of butyl glycidyl ether, stir well and pour into a mold to cure to obtain a sheath filler", and the other steps remain unchanged, and the prepared water-resistant aluminum alloy core photovoltaic cable is recorded as 3.
[0039] Comparative Example 4: Compared with Example 1, the difference of Comparative Example 4 is that step S2 is not performed, and the copolymer is replaced by hydroxypivalic acid neopentyl glycol monoester in step S3, specifically "S3.3: after uniform dispersion, add 0.1 mass parts of Tween 80, 2.5 mass parts of 593 curing agent and 6 mass parts of hydroxypivalic acid neopentyl glycol monoester, stir well and pour into a mold to solidify to obtain a sheath filler", and the other steps remain unchanged, and the prepared water-resistant aluminum alloy core photovoltaic cable is recorded as 4.
[0040] Comparative Example 5: Compared with Example 1, the difference of Comparative Example 5 is that, in step S2.1, neopentyl glycol hydroxypivalate is not added, but neopentyl glycol is used instead of neopentyl glycol hydroxypivalate, specifically "S2.1: weigh 2 parts by mass of neopentyl glycol in a reaction bottle, then add 8 parts by mass of anhydrous methanol, dissolve, vacuum and pass nitrogen", and the other steps remain unchanged, and the prepared water-resistant aluminum alloy core photovoltaic cable is recorded as 5.
[0041] Comparative Example 6: Compared with Example 1, the difference of Comparative Example 6 is that no palygorskite powder is added in step S3.2, specifically "S3.2: weigh 10 parts by mass of modified epoxy resin, add it to the reactor, then heat the reactor to 40°C, magnetically stir for 15 minutes, then add 0.5 parts by mass of modified magnesium hydroxide, 0.2 parts by mass of cotton fiber, 1 part by mass of hollow glass microbeads and 1 part by mass of silane coupling agent KH550 in sequence, continue stirring at 40°C for 2 hours, and ultrasonically disperse the mixture for 30 minutes", and the other steps remain unchanged, and the prepared water-resistant aluminum alloy core photovoltaic cable is recorded as 6.
[0042] Comparative Example 7: Compared with Example 1, the difference of Comparative Example 7 is that cotton fiber is not added in step S3.2, specifically "S3.2: weigh 10 parts by mass of modified epoxy resin, add it to the reactor, then heat the reactor to 40°C, magnetically stir for 15 minutes, then add modified magnesium hydroxide, 0.5 parts by mass of palygorskite powder, 1 part by mass of hollow glass microbeads and 1 part by mass of silane coupling agent KH550 in sequence, continue stirring at 40°C for 2 hours, and ultrasonically disperse the mixture for 30 minutes", and the other steps remain unchanged, and the prepared water-resistant aluminum alloy core photovoltaic cable is recorded as 7.
[0043] The tensile strength and elongation at break of Examples 1-3 and Comparative Examples 1-7 were tested, as shown in Table 1.
[0044]
[0045] Table 1
[0046] After soaking in water, Examples 1-3 and Comparative Examples 1-7 were placed in an aging box for 7 days to test the aging degree. The results are shown in Table 2.
[0047] Table 2
[0048] It can be seen from Table 1 that the tensile strength of Examples 1-3 is above 22.3 MPa, and the elongation at break is above 314%, while the tensile strength of Comparative Example 1 is 17.1 MPa, and the elongation at break is 303%, and the tensile strength of Comparative Example 2 is 19.8 MPa, and the elongation at break is 301%. It can be seen that the addition of silica modified with perfluorooctane sulfonic acid brings about an improvement in the mechanical strength of the cable filler, while perfluorooctane sulfonic acid cannot achieve a better effect than perfluorooctane sulfonic acid. The tensile strength of Comparative Example 3 is 16.3 MPa, and the elongation at break is 267%, and the tensile strength of Comparative Example 2 is 19.8 MPa, and the elongation at break is 301%. The tensile strength of Example 4 is 17.6 MPa, and the elongation at break is 277%. The tensile strength of Example 5 is 18.9 MPa, and the elongation at break is 281%, indicating that the copolymer formed by combining hydroxypivalic acid neopentyl glycol monoester and butyl glycidyl ether brings better mechanical properties and flexibility. The tensile strength of Example 6 is 15.2 MPa, and the elongation at break is 283%. The tensile strength of Example 7 is 14.7 MPa, and the elongation at break is 285%. It can be seen that without the addition of palygorskite and cotton fiber, the flexibility of the cable filler will be greatly reduced.
[0049] As can be seen from Table 2, Examples 1-3 showed no blackening and oxidation after the water aging test, while Comparative Examples 1-7 showed varying degrees of oxidation blackening. It can be seen that the copolymer added in the present invention and the surface-modified silica with perfluorooctane sulfonic acid have the effect of improving the heat resistance and water resistance of the filler, so that the cable did not show oxidation blackening in the water aging test.
[0050] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A preparation process for a water-resistant aluminum alloy core photovoltaic cable, characterized in that: The steps include: S1: Preparation of modified epoxy resin Adding silica and perfluorooctane sulfonic acid into deionized water, and then adding silane coupling agent KH570 to obtain perfluorooctane sulfonic acid surface-modified silica, weighing epoxy resin, perfluorooctane sulfonic acid surface-modified silica and silane coupling agent KH550, adding them into anhydrous ethanol for reaction, and obtaining modified epoxy resin; S2: Preparation of copolymers from hydroxypivalic acid neopentyl glycol monoester and butyl glycidyl ether Dissolving hydroxypivalic acid neopentyl glycol monoester and anhydrous methanol, then adding potassium methoxide and anhydrous methanol, and then adding glycerol and butyl glycidyl ether to react to obtain a copolymer; S3: Preparation of cable sheath filler Magnesium hydroxide, deionized water and sodium oleate are weighed and reacted to obtain modified magnesium hydroxide, modified epoxy resin, modified magnesium hydroxide, palygorskite powder, cotton fiber, hollow glass microspheres and silane coupling agent KH550 are reacted, and Tween 80, 593 curing agent and copolymer are added to prepare a sheath filler; S4: Preparation of water-resistant aluminum alloy core photovoltaic cables Aluminum alloy is used as the cable core material, the outer layer of the cable core material is wrapped with an insulating layer, the outer layer is filled with the sheath filler prepared in step S3, and the outermost layer is wrapped with a cable sheath to obtain a water-resistant aluminum alloy core photovoltaic cable.
2. The preparation process of a water-resistant aluminum alloy core photovoltaic cable according to claim 1, characterized in that: Step S1 prepares a modified epoxy resin, comprising the following steps: S1.1: Add 10-15 parts by mass of silica and 20-25 parts by mass of perfluorooctane sulfonic acid to 75-85 parts by mass of deionized water, perform ultrasonic treatment for 20-25 minutes, then add 2-5 parts by mass of silane coupling agent KH570, and react for 3-4 hours in a water bath at 40-50°C. After the reaction is completed, pour out the liquid in the flask, filter it, wash it, dry it, and grind it to obtain perfluorooctane sulfonic acid surface-modified silica, which is stored for later use; S1.2: Weigh 50-60 parts by mass of epoxy resin, 2-5 parts by mass of perfluorooctane sulfonic acid surface-modified silica and 15-20 parts by mass of silane coupling agent KH550, add them to 75-90 parts by mass of anhydrous ethanol, heat to 50-60°C in a water bath, maintain stirring at a speed of 50-60r / min, react for 4-5h, then remove the solvent anhydrous ethanol, wash and dry to obtain the modified epoxy resin.
3. The preparation process of a water-resistant aluminum alloy core photovoltaic cable according to claim 2, characterized in that: Step S2: preparing a copolymer from hydroxypivalic acid neopentyl glycol monoester and butyl glycidyl ether, comprising the following steps: S2.1: Weigh 2-3 parts by weight of neopentyl glycol monohydroxypivalate into a reaction bottle, add 8-10 parts by weight of anhydrous methanol, dissolve, and evacuate and pass nitrogen; S2.2: Mix potassium methoxide and anhydrous methanol at a solid-liquid ratio of (0.5-1) g:2 mL and add them to the reaction bottle, then stir for 2-2.5 h, and then remove the solvent methanol; S2.3: Heat the reaction bottle to 90-95°C, mix 0.5-1 parts by mass of glycerol and 1-2 parts by mass of butyl glycidyl ether, add them into the reaction bottle, and stir mechanically at a speed of 100-120 r / min for 12-13 hours; S2.4: Then terminate the reaction, add 10-15 parts by mass of anhydrous methanol to the product and mix well, then dialyze using a dialysis bag with a molecular weight cutoff of 1200 g / mol, use methanol for 48-50 hours, then use a rotary evaporator to spin dry the methanol, and put it into a vacuum drying oven at 40-45°C to obtain a copolymer.
4. The process for preparing a water-resistant aluminum alloy core photovoltaic cable according to claim 3, characterized in that: Step S3 prepares the cable sheath filler, comprising the following steps: S3.1: Weigh 7-8 parts by mass of magnesium hydroxide, 90-95 parts by mass of deionized water and 4-5 parts by mass of sodium oleate, pour them into a three-necked flask in sequence, react in a water bath at 40-45°C for 2-3 hours, and after the reaction is complete, pour out the liquid in the flask, filter it, wash, dry it, and grind it to obtain modified magnesium hydroxide for standby use; S3.2: Weigh 10-15 parts by mass of modified epoxy resin, add it into the reactor, then heat the reactor to 40-45°C, stir it magnetically for 15-20 minutes, then add 0.5-1.5 parts by mass of modified magnesium hydroxide, 0.5-1 parts by mass of palygorskite powder, 0.2-0.6 parts by mass of cotton fiber, 1-3 parts by mass of hollow glass microspheres and 1-3 parts by mass of silane coupling agent KH550 in sequence, continue stirring at 40-50°C for 2-3 hours, and then ultrasonically disperse for 30-35 minutes; S3.3: After uniform dispersion, add 0.1-0.3 parts by mass of Tween 80, 2.5-3 parts by mass of 593 curing agent and 6-10 parts by mass of copolymer, stir evenly and pour into a mold to solidify to obtain a sheath filler.
5. The process for preparing a water-resistant aluminum alloy core photovoltaic cable according to claim 4, characterized in that: The silane coupling agent KH550 is specifically a functional material modifier with γ-aminopropyltriethoxysilane as a main component.
6. The process for preparing a water-resistant aluminum alloy core photovoltaic cable according to claim 4, characterized in that: Tween 80 is specifically a polyoxyethylene sorbitan monooleate nonionic surfactant.
7. The process for preparing a water-resistant aluminum alloy core photovoltaic cable according to claim 4, characterized in that: The 593 curing agent is specifically a modified amine curing agent synthesized by the reaction of diethylenetriamine and butyl glycidyl ether.
8. The process for preparing a water-resistant aluminum alloy core photovoltaic cable according to claim 4, characterized in that: The insulating layer is made of one of polyethylene, cross-linked polyethylene and polypropylene.
9. The process for preparing a water-resistant aluminum alloy core photovoltaic cable according to claim 4, characterized in that: The cable sheath is made of one of thermoplastic polyurethane elastomer rubber, silicone rubber, chlorinated polyethylene and polyvinyl chloride materials.
10. A water-resistant aluminum alloy core photovoltaic cable, which is prepared by the preparation process of the water-resistant aluminum alloy core photovoltaic cable according to any one of claims 1 to 9.
Citation Information
Patent Citations
Attapulgite adhesive for construction and preparation method thereof
CN106927757A
Wear-resistant anti-drag silicone rubber skeleton oil seal
CN109553977A
Spray-coating damping coating for ships and preparation method= thereof
CN111548721A
Process for the manufacture of mixtures of linear highpolymeric organosiloxanes with fillers
GB1325654A
Dendritic polymers with enhanced amplification and interior functionality
SG136667A1